2023
DOI: 10.1101/2023.01.06.522942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic limitations on brain oxygen metabolism: physiological implications

Abstract: A recent hypothesis is that maintaining the brain tissue ratio of O2 to CO2 is critical for preserving the entropy increase available from oxidative metabolism of glucose, with a fall of that available entropy leading to a reduction of the phosphorylation potential and impairment of brain energy metabolism. The hypothesis suggests that physiological responses under different conditions can be understood as preserving tissue O2/CO2. To test this idea, a mathematical model of O2 and CO2 transport was used to cal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…We assessed whether this criterion alone could predict the experimental values of NVC coupling and OEF 0 . As shown in Figure S6A, and in agreement with Buxton (2021Buxton ( , 2023, the value of pO T 2 /pCO T 2 during activation is highly dependent on the NVC constant being close to uniform at the experimental value of n = 2.28 when OEF 0 is also at its experimental mean value of 0.42. However, as shown in Figure S6B,C, when n = 2.28, the pO T 2 /pCO T 2 ratio as a function of CMRO 2 ′ is close to constant regardless of large variations in OEF 0 and R glyc .…”
Section: Maintenance Of the Po T 2 /Pco T 2 Ratiosupporting
confidence: 82%
See 3 more Smart Citations
“…We assessed whether this criterion alone could predict the experimental values of NVC coupling and OEF 0 . As shown in Figure S6A, and in agreement with Buxton (2021Buxton ( , 2023, the value of pO T 2 /pCO T 2 during activation is highly dependent on the NVC constant being close to uniform at the experimental value of n = 2.28 when OEF 0 is also at its experimental mean value of 0.42. However, as shown in Figure S6B,C, when n = 2.28, the pO T 2 /pCO T 2 ratio as a function of CMRO 2 ′ is close to constant regardless of large variations in OEF 0 and R glyc .…”
Section: Maintenance Of the Po T 2 /Pco T 2 Ratiosupporting
confidence: 82%
“…Using Monte Carlo and sensitivity analysis we found that optimization of n and OEF 0 with the objective of minimizing deviations in the levels of pH, pCO 2 , and pO 2 resulted in a narrow range of values similar to those measured in vivo. In contrast to previous work, in which variations in pO 2 or pO T 2 ∕ pCO T 2 were minimized (Buxton, 2010(Buxton, , 2021Buxton, 2023;Gjedde, 2005), OEF 0 did not have to be assumed.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Early studies using positron emission tomography (PET) have demonstrated that a modest increase in CMRO2 is accompanied by a much larger increase in CBF (Fox et al, 1988;Fox & Raichle, 1986), resul ng in a ∆CBF/∆CMRO2 ra o (n-ra o) of approximately 2-4 and, consequently, a posi ve BOLD response (Ances et al, 2008;Buxton, 2010;Uludağ et al, 2004). Although the regulatory mechanisms of this hemodynamic response are s ll subject to debate (A. D. Ekstrom, 2021;Hillman, 2014), this overcompensa ng CBF likely maintains the par al pressure of oxygen in capillaries to allow diffusion into brain ssue (Buxton, 2020(Buxton, , 2023DiNuzzo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%